2016
DOI: 10.1136/bcr-2016-214629
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted treatment of pilonidal disease, using a combination of diathermy ablation and phenol application

Abstract: Video-assisted diathermy ablation (VADA) and crystallised phenol application (CPA) have been independently suggested as minimally invasive treatment options for sacrococcygeal pilonidal disease (SPD). The failure rates may be 5-33% with either method, and these methods have a longer healing time when used alone. Thus, we combined the two methods to fulgurate the infected inner lining of the sinus after cleaning up the hair and debris, and to identify the anatomy of the pilonidal cavity in its entirety, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…In fact, since its introduction, this approach has gained momentum among surgeons because of relatively absent postoperative pain, good aesthetic results, low infection rate, and low long-term recurrence rate (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, since its introduction, this approach has gained momentum among surgeons because of relatively absent postoperative pain, good aesthetic results, low infection rate, and low long-term recurrence rate (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…The techniques mentioned above are blind methods, for this reason, recently, researchers have started to apply a combined treatment method by adding video-assisted or EPSiT procedures. In this way, they reported that the sinus anatomy would be evaluated better, all the hairs could be cleaned, and it would be ensured that the entire epithelium was destroyed [5,13,[16][17][18][19][20]. We performed the laser-EPSiT combination with the same goals and achieved successful results.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, laser applications have also been used for the treatment of PSD [5,[13][14][15][16][17]. And nowadays, efforts are still ongoing to find the optimal treatment by combining the listed methods [5,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Recurrence rates have been reported to be lower than standard excisional operations [61]. Modifications include the injection of phenol in the tract [62,63]. When compared to the traditional Limberg flap, endoscopic treatment of pilonidal disease may have higher recurrence rates but is associated with fewer postoperative complications [64].…”
Section: Endoscopic/video-assisted Ablation Of Pilonidal Sinus (Vaaps)mentioning
confidence: 99%